PERANCANGAN PERMUKIMAN KAMPUNG AUR DI KOTA MEDAN (DENGAN PENDEKATAN ARSITEKTUR PERILAKU DAN LINGKUNGAN) - Sembiring, Dicky Andrea (Jurnal Koridor, 2017)
Kampung Aur is one of the densely populated settlements situated on the banks of the Deli River, Medan. So far there have been several type of solution to the matter regarding densely populated settlements ranging from forced evictions, construction of new settlements in the form of flat / rusunawa and kampung improvement program. It can be said, the government began to realize that the problem can not be solved with one-way system. There must be communication with the slum dwellers. This then prompted the authors to make the planning of Kampung Aur settlements with environmental-behavioral approach to be the title of his thesis. This study aims to produce a design of settlement which can accommodate social and cultural aspects of society through environmental behavior approach. To achieve these objectives, participatory observation will be conducted on each dominant communities that exist on the site. Through these observations it will be known how the environmental setting and behavior setting works in Kampung Aur. The data of environmental setting and behavior setting will then be processed to produce design criteria of Kampung Aur Settlement. From this research it was found that there are two dominant tribe in Kampung Aur, the Chinese and Minang. Minang communities further demonstrate characteristics that have a high degree of territoriality and low privacy, while Chinese are just the opposite. Based on the characteristics of the existing society, a desing can be produced in accordance with the behavior of each communities in Kampung Aur.